VALUASI EKONOMI LINGKUNGAN NILAI GUNAAN LANGSUNG DAN TIDAK LANGSUNG KOMODITAS EKONOMI - Bernard Hasibuan (Signifikan: Jurnal Ilmu Ekonomi, 2014)
Natural phenomenon which is the impact of humans on the environment management is already affecting economic system. The impact of climate change on the agricultural sector, especially in Indonesia is increasingly felt. These changes are indicated by the floods, droughts, shifting the rainy season. The economic value of agricultural commodities that were examined included the value of use of direct and indirect use of value. For agricultural natural resources that have used market price calculation Effect on Production (EOP). This study use CVM method. The views of Lombok on climate change phenomenon quite good, the majority (75%) community to know the phenomenon of climate change. Public response to this phenomenon very well where the desire to improve the situation so big that 76% would like to improve or unable to pay for the improvement in the state even though their incomes are very low at 70% below the provincial minimum wage. Preferences people who want to improve this situation is a reflection of their needs and desires to escape from the problems of climate change impacts.DOI: 10.15408/sjie.v3i2.2055